2020
DOI: 10.3390/nu12092550
|View full text |Cite
|
Sign up to set email alerts
|

Could Vitamins Help in the Fight Against COVID-19?

Abstract: There are limited proven therapeutic options for the prevention and treatment of COVID-19. The role of vitamin and mineral supplementation or “immunonutrition” has previously been explored in a number of clinical trials in intensive care settings, and there are several hypotheses to support their routine use. The aim of this narrative review was to investigate whether vitamin supplementation is beneficial in COVID-19. A systematic search strategy with a narrative literature summary was designed, using the Medl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
198
0
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(249 citation statements)
references
References 188 publications
1
198
0
24
Order By: Relevance
“…In addition to its role in cellular and humoral immunity, vitamin D, similar to zinc and vitamin C, plays an important role in the formation and maintenance of epithelial and endothelial barriers, including lung tissue (17,19,(144)(145)(146). Using a vitamin D receptor knockout mouse model, Chen et al (146) observed that in the absence of this hormone signaling, the animals exhibited lung inflammation and impaired lung function, which can be explained by the increased pulmonary permeability resulting from impairment of the integrity of the epithelial barrier.…”
Section: Vitamin Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its role in cellular and humoral immunity, vitamin D, similar to zinc and vitamin C, plays an important role in the formation and maintenance of epithelial and endothelial barriers, including lung tissue (17,19,(144)(145)(146). Using a vitamin D receptor knockout mouse model, Chen et al (146) observed that in the absence of this hormone signaling, the animals exhibited lung inflammation and impaired lung function, which can be explained by the increased pulmonary permeability resulting from impairment of the integrity of the epithelial barrier.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Inadequate nutrition is considered a contributing factor to the emergence of viral infection due to its contribution to weakness of immune system, which increases the rate of infections and the risk of mortality and morbidity. Moreover, viral infections increase the demand for several micronutrients such as vitamin A, B, C, D, zinc, and selenium (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…with doses between 2 and 8 g/day in hospitalised patients due to increased need when fighting a viral infection as concluded by three recent reviews. [128] [129] [130] People in high-risk groups for COVID-19 mortality, and at risk of vitamin C deficiency, should be encouraged to supplement with vitamin C daily to ensure vitamin C adequacy at all times, and to increase the dose when virally infected to up to 6-8 g/day [131]. Whether or not this will prevent conversion to the critical phase in COVID-19 has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B [7] This is a group of water-soluble vitamins. Vitamin B6 (pyridoxine) and B12 (cobalamin) play an important role in the innate and adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%